BAHASA ETNIK MADURA DI LINGKUNGAN SOSIAL: KAJIAN SOSIOLINGUISTIK DI KOTA SURAKARTA - Saddono, Kundharu (Universitas Muhammadiyah Surakarta, 2006)
This research was descriptive about language used by Madurese ethnic in Surakarta. The locations selected were five sub-districts of Surakarta: Jebres, Pasar Kliwon, Serengan, Banjarsari, and Laweyan. The research was aimed to describe the language used by Madurese society in Surakarta based on social domain, to explain the type and the function of language of the Madurese society based on social domain, and to explain the language specification of Madurese society in Surakarta. The data collection was conducted through listening and oral method. This method was supported by recording and a note technique. In addition, in- depth interview technique was used. The data were analyzed by using sociolinguistics approach by considering the social context of the speech components (Hymeâs SPEAKING). The results shows that the functions of Madurese language are familiness, expression of feeling, ethnic identity, secrecy, and cultural defense; Javanese language is used for habit, adaptation, and friendship; Indonesian lan- guage is used for formal situation, ethnic community, education situation, initial meeting; mixed language is used for nonformal situation, message confirmation, and new concepts. The specifications of the language use of the Madurese ethnic community in Surakarta are the use of greeting, use of particles, use of reduplica- tions, type of words, language variation, and Bangkalan dialect.Â Key words: bilingualisme, madurese ethnic, sociolinguistic, dan dialek.